Analysis of Underground Lined Rock Cavern - V. Sharma, I.; Pallavi Badry, Dr. (International Journal of Engineering and Technology, 2018)
Underground storage excavation can be done either by access tunnel or by access shaft or the combinations of both. Other factors depend of land availability, surrounded by cavern site and also the depth of the cavern is the most important considerations. Â The caverns are generally built in rock where it offers the good support but need to analyze for the stress condition accurately.Â Â In this study the cavern along with the tunnel is analyzed for static analysis and the results are compared for both linear and nonlinear condition for the stage analysis. It has been found that the soil shows different stress condition with respect to special variation andÂ the analysis method.Â Â